Wewenang Satuan Polisi Pamong Praja dalam Penegakan Peraturan Daerah Dengan Berlakunya Peraturan Pemerintah Nomor 6 Tahun 2010 di Kabupaten Badung - Agus Wandayuda; I Gusti Bagus Suryawan; I Nyoman Sutama (Jurnal Analogi Hukum, 2020)
The Civil Service Police Unit is a regional apparatus organization in enforcing the Regional Regulation and holding public order as stipulated in the Republic of Indonesia Government Regulation Number 6 of 2010 concerning the Civil Service Police Unit having the authority to act in carrying out a non-judicial order for the community or a legal entity's violation of Regional Regulations and Regional Head Regulations. The formulation of the problems that can be used for this research are: (1) What is the duty and authority of the Civil Service Police Unit in the enforcement of Regional Regulations with the enactment of Government Regulation Number 6 of 2010 in Badung Regency; (2) Any possible factors that make obstacles in the Enforcement of Regional Regulations in Badung Regency carried out by the Civil Service Police Unit. This research was conducted using normative legal research. The source and type of material of this study are primary, namely looking at legislation and secondary materia,l written by experts and the results of the scientists are then processed and analyzed descriptively to obtain a conclusion. Based on the results of the study, it can be concluded that the Satpol PP officers are part of the Regional Apparatus who carry out their duties and authorities in accordance with statutory provisions, namely in Article 148 of Law Number 23 Year 2014, that the obstacles faced by Satopl PP in Badung Regency are many shops modern people who have not fulfilled the licensing requirements in full as the provisions set by Badung Regency, so that in carrying out their duties the Satpol PP often experiences clashes with relevant agencies and the community. Suggestions given by the authors are expected to have a synergy between the Satpol PP and the relevant agencies so that in terms of enforcing regulations and order will go well so that the impression of arrogance from Satpol PP officers in carrying out their duties does not develop in the community.